Finding true north: firsthand stories of the booms that built modern Alaska - Rettig, Molly, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2021)
Molly Rettig leads readers through pivotal moments in modern Alaska's history that have not only built the Alaska we see today, but also created moments of great contention such as gold and oil. She ties the stories of people who lived during these times to her own story of discovery and change. The book starts with her arrival to Alaska, naive and unaware, where readers will learn and evolve with her as she comes to new realizations.--Provided by publisher.
Gold -- Air -- Oil -- Subsistence.
Keywords: Rettig, Molly; Alaska Natives -- Biography; Alaska -- History; Gold mines and mining -- Alaska -- History; Alaska -- Description and travel; Petroleum industry and trade -- Alaska -- History; Alaska -- Biography